SIFAT FISIK PAPAN BUATAN DARI LIMBAH TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jacq) DAN SERBUK GERGAJIAN KAYU GALAM (Melaleuca cajuputi Powell) - Silviana Puji Astutik; Muhammad Faisal Mahdie; Yuniarti Yuniarti (Universitas Lambung Mangkurat, 2020)
The need for board materials is currently experiencing a very drastic increase as the population in the world increases, especially Indonesia. Increasing the demand for boards resulted in diminishing forest resources. One way to overcome this problem is the efficiency of using wood through the manufacture of waste boards from industry or other lignocellulosic materials into particle boards which are relatively inexpensive materials obtained without reducing their quality or quality. This research to determine the physical properties (moisture content, density, shrinkage and thickness development) of empty palm oil and galam sawdust (Melaleuca cajuputi Powell). The results of the test made by OPEFB waste board and sawdust of galam wood have a water content value ranging from 9.16 - 10.92%, the density ranges from 0.42 - 0.55 g / cm³, the thick development ranges from 7.74 - 37.47%, shrinkage ranges from 1.59 - 4.51%. Only the water content and density values that meet SNI 03-2105-2006 while in the thick development only treatment A, C, and D that meet SNI 03-2105 2006. The composition of raw materials has a significant effect on the treatment of density values and very significant effect on the treatment value the development of thick, ambush. The best artificial boards are artificial boards and the composition is 100% natural because the average yield meets SNI 03-2105-2006. My advice should be further research on the same ingredients but with different adhesive concentrations.Keywords; Artificial Board; Waste; Quality